ZD7288 Enhances Long-Term Depression at Early Postnatal Medial Perforant Path-Granule Cell Synapses - Xiati Guli; Tursonjan Tokay; Marco Rohde; Roland A. Bender; Rüdiger Köhling; Timo Kirschstein (Neural Plasticity)
Hyperpolarization-activated, cyclic nucleotide-gated nonselective (HCN) channels modulate both membrane potential and resistance and play a significant role in synaptic plasticity. We compared the influence of HCN channels on long-term depression (LTD) at the medial perforant path-granule cell synapse in early postnatal (P9–15) and adult (P30–60) rats. LTD was elicited in P9–15 slices using low-frequency stimulation (LFS, 900 pulses, 1 Hz; 80±4% of baseline). Application of the specific HCN channel blocker ZD7288 (10 μM) before LFS significantly enhanced LTD (62±4%; P<0.01), showing HCN channels restrain LTD induction. However, when ZD7288 was applied after LFS, LTD was similar to control values and significantly different from the values obtained with ZD7288 application before LFS (81±5%; P<0.01), indicating that HCN channels do not modulate LTD expression. LTD in slices from adult rats were only marginally lower compared to those in P9–15 slices (85±6%), but bath application of ZD7288 prior to LFS resulted in the same amount of LTD (85±5%). HCN channels in adult tissue hence lose their modulatory effect. In conclusion, we found that HCN channels at the medial perforant path-granule cell synapse compromise LFS-associated induction, but not expression of LTD in early postnatal, but not in adult, rats.